CONSUMER KNOWLEDGE, ATTITUDE, ENVIRONMENT AND INCOME TOWARD COOKING OIL WASTE - Azteria, Veza; Sayyid M, Muhammad; Handayani, Putri; Angeliana K, Devi (Universitas Medan Area, 2024)
Used cooking oil is waste oil that comes from a type of cooking oil that has been used repeatedly. If not managed properly, it can become a source of environmental pollution. Managing used cooking oil still needs to be in a good category. Preliminary studies from this research found that as many as 60% of people in the Cengkareng Village area, West Jakarta, need to manage used cooking oil properly. This research aims to determine factors related to knowledge, attitudes, income and environment in managing used cooking oil. The sample used was 141 homemakers using purposive sampling. The data collection methods used were interviews and observation. This research uses independent variables (Knowledge, Attitudes, Income Level, and Environment) and dependent variables (Used cooking oil management behaviour). The analysis used is descriptive analysis with the chi-square test. Based on the research results, it was found that the highest proportion of used cooking oil management behaviour was poor (51.1%), good knowledge (54.6%), negative attitude (60.3%), sufficient income level (81.6%), and bad environment (93.6%). %). There is a relationship between knowledge (p-value = 0.001) and community behaviour in managing used cooking oil and a relationship between attitude (p-value = 0.001) and behaviour in the community driving used cooking oil. There is a need for interaction and cooperation between societal stakeholders to improve public awareness of cooking oil management to create a zero-waste environment.